Early closure of fistula using neo-adjuvant intra-arterial chemotherapy in locally advanced anal cancer. Issue 11 (November 2017) - Cacheux, Wulfran; Koessler, Thibaud; Puppa, Giacomo; Fernandez, Eugenio; Ho, Lisa; Dietrich, Pierre-Yves; Zilli, Thomas; Allal, Abdelkarim Said; Roche, Bruno; Ris, Frederic; Roth, Arnaud
Abstract: Background: Locally advanced anal cancer patients, especially with T4 disease and fistula, have a dismal prognosis. Neo-adjuvant intra-arterial chemotherapy before standard chemoradiation has been shown to be promising in this setting. Aims: We are reporting results from a larger patient population. Methods: From 2005 to 2015, 25 consecutive patients with locally advanced anal cancer, 18 of them fistulised, received intra-arterial chemotherapy. Results: Twenty-two of 25 patients (88%) had T4N0-3 disease and 3 (12%) T3N3. An objective tumour response was observed in 24 of 25 patients (96%): 24 partial responses and 1 with stable disease. Fistulas' complete closure was observed in 15 of 18 patients (83.3%). Following intra-arterial chemotherapy, 23 patients underwent chemoradiation. Twenty-one of 25 patients (84%) had a complete remission 6 months after treatment completion. Amongst 22 patients followed for 3 or more years, 18 of them (81%) are colostomy free at 3 years. Five-year overall survival is 75%. Most frequent grade 3–4 toxicity of IAC was neutropenia (25%). Conclusions: Neo-adjuvant intra-arterial chemotherapy combined to chemoradiation resulted in a high rate of fistulas closure and long-term control of locally advanced anal cancer. This interesting approach in the treatment of fistulised anal cancer, needs a prospective study before being considered a new standard strategy.